PENILAIAN TERHADAP BATAL ATAU TIDAK SAHNYA SUATU KEPUTUSAN DAN/ATAU TINDAKAN ADMINISTRASI PEMERINTAHAN - Hidayat Pratama Putra (Jurnal Hukum Peratun, 2020)
The concept of Nullity (Nietigheid) is very important in administrative law because of the validity of a government act (bestuurshandelingen) either in the form of a decision (besluit) or in the form of an action (Feitelijk Handelingen) depends on the existence of the doctrine regarding Nullity. Since when is a decision declared invalid, and what are the legal consequences, if this is answered by the existence of this Nullity doctrine. Law No. 30 of 2014 concerning Government Administration, has more or less changed the paradigm regarding the teachings of annulment from the one held by administrative law experts in Indonesia, especially with regard to the doctrine of abuse of power, which is regulated in several articles in the Government Administration Law. In this paper, it is found that government decisions and/or actions that are canceled or declared invalid have different consequences. This paper uses a normative juridical research method, namely using secondary data in the form of primary and secondary sources of law, both applicable laws and related literature.